2004
DOI: 10.1007/s00264-004-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Chondral degeneration and therapeutic hip arthroscopy

Abstract: Therapeutic hip arthroscopy for the treatment of chondral degeneration remains controversial. A retrospective cohort study examined 70 patients of mean age 47 (range 22-87) years who had undergone hip arthroscopy and assessed them for evidence of chondral degeneration using radiological and arthroscopic means. Clinical outcome was assessed using a modified Farjo and Glick classification. Thirty-nine patients had evidence of chondral degeneration on arthroscopy with or without radiological diagnosis, and 31 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
2
20
1
Order By: Relevance
“…Similar to our study, Horisberger et al reported a 60% (12 patients) failure rate using non-arthritic hip score (NAHS) in 20 patients with radiographic OA (Tonnis Grades 1-3) at a mean last followup of 3 years [14]. Most studies evaluating hip arthroscopy in the setting of OA predate FAI bony resections [4,8,13,17,18,23,27,35] ( Table 6). Margheritini and Villar [23] evaluated 133 patients with hip OA who underwent hip arthroscopy and reported a 39% failure rate at a mean followup of 18 months using the HHS.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar to our study, Horisberger et al reported a 60% (12 patients) failure rate using non-arthritic hip score (NAHS) in 20 patients with radiographic OA (Tonnis Grades 1-3) at a mean last followup of 3 years [14]. Most studies evaluating hip arthroscopy in the setting of OA predate FAI bony resections [4,8,13,17,18,23,27,35] ( Table 6). Margheritini and Villar [23] evaluated 133 patients with hip OA who underwent hip arthroscopy and reported a 39% failure rate at a mean followup of 18 months using the HHS.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we found that a greater duration of symptoms preoperatively was an independent predictor of poorer scores and higher failure rates, and increasing MRI chondral grade was an independent predictor of poorer scores (Tables 3-5). Two prior studies report increased failure rates with greater degrees of intraoperative chondral disorders in the presence of preoperative radiographic OA [8,35]. In addition, Margheritini and Villar [23] found that greater age was predictive of a poorer HHS for HHS = Harris hip score; NAHS = non-arthritic hip score; JOA = Japanese orthopaedic association pain score; A = longer duration of symptoms; B = greater preoperative joint space narrowing/OA grade; C = greater intraoperative chondral damage; D = greater age; NA = not available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations